2020
DOI: 10.1111/sed.12711
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization pathways in the Great Artesian Basin (Australia) spring mound carbonates: Implications for life signatures on Earth and beyond

Abstract: Recent studies of continental carbonates revealed that carbonates with similar fabrics can be formed either by biotic, biologically‐induced, biologically‐influenced or purely abiotic processes, or a combination of all. The aim of this research is to advance knowledge on the formation of carbonates precipitated (or diagenetically altered) in extreme, continental environments by studying biotic versus abiotic mechanisms of crystallization, and to contribute to the astrobiology debate around terrestrial analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 127 publications
(218 reference statements)
0
19
0
Order By: Relevance
“…Similar formation processes, from nanocrystals to fibrous crystals with a radial arrangement, are common during the formation of marine invertebrate hardparts, (e.g. corals and mollusks; Stolarski and Mazur, 2005;Holcomb et al, 2009;Cohen and Holcomb, 2015) and have also been described in terrestrial spring carbonates (Pedley, 2014;Jones, 2017a, Jones, 2017bFranchi and Frisia, 2020).…”
Section: Formation Process From Micritic Nuclei To Botryoidal and Spherulitic Aragonitementioning
confidence: 68%
See 1 more Smart Citation
“…Similar formation processes, from nanocrystals to fibrous crystals with a radial arrangement, are common during the formation of marine invertebrate hardparts, (e.g. corals and mollusks; Stolarski and Mazur, 2005;Holcomb et al, 2009;Cohen and Holcomb, 2015) and have also been described in terrestrial spring carbonates (Pedley, 2014;Jones, 2017a, Jones, 2017bFranchi and Frisia, 2020).…”
Section: Formation Process From Micritic Nuclei To Botryoidal and Spherulitic Aragonitementioning
confidence: 68%
“…In the three case studies, the change in crystal size and morphology from nanocrystals to botryoidal and spherulitic fabrics may be driven by: 1) thermodynamic processes referred to as "Ostwald ripening," where smaller crystals dissolve and reprecipitate as larger crystals with the same mineralogy in order to reduce free surface energy (Ostwald, 1897;Kirkland et al, 1999;Franchi and Frisia, 2020); 2) high Mg/Ca ratios favoring fibrous growth (Folk, 1974(Folk, , 1994Jones, 2017a, Jones, 2017b; and 3) decreasing organic components from nanocrystals to fibrous crystals (Stolarski and Mazur, 2005). In summary, the botryoidal and spherulitic aragonite in this study are formed via replacement (Abu Dhabi) or primary precipitation via aggregation of nanocrystal aragonite precipitates (Bagni San Filippo and Great Salt Lake).…”
Section: Formation Mechanisms Of Botryoidal and Spherulitic Aragonite: Replacement And Precipitationmentioning
confidence: 99%
“…Continental carbonates are also useful proxies for the characterisation of fluid/rock interactions between the groundwater, formation water and the rock substratum (Kokh et al, 2017;Teboul et al, 2016;Uysal et al, 2007Uysal et al, , 2009 and for the characterisation of the sources of major and trace elements that constitute the spring deposits (Brogi et al, 2016(Brogi et al, , 2020Teboul et al, 2016). Continental carbonates have the potential to illustrate the evolution of non-marine organisms from the Archean to present as well as provide evidence for non-marine life during periods of intense climate and environmental stress (Capezzuoli et al, 2010;Smith et al, 2004aSmith et al, , 2004b and valuable information about non-classical crystallization pathways with important ramifications for astrobiological research (see discussion in Franchi & Frisia, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study of microbial biofilms and microbial mats in warm to hot hydrothermal vent environments and their interaction with siliceous and carbonate mineral precipitation is linked to the understanding of early life forms on Earth and could also be important for the search of biosignatures on putative habitable planets and moons (cf. Cady and Farmer, 1996; Farmer, 1998; Reysenbach et al, 1999; Westall et al, 2000; Reysenbach and Cady, 2001; Reysenbach and Shock, 2002; Rothshield and Mancinelli, 2001; Cady and Noffke, 2009; Ruff and Farmer, 2016; Cady et al, 2018; Reinhardt et al, 2019; Sanchez-Garcia et al 2019; Franchi and Frisia, 2020). Geomicrobiological research on the origin of life has recently shifted from very high temperature submarine Black Smokers to terrestrial thermal springs, because the relatively lower temperatures of terrestrial geothermal sites facilitate the preservation of organic molecules (Des Marais and Walter, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on present-day marine and terrestrial settings, from the geological record and laboratory experiments have demonstrated that carbonate mineral precipitation associated with microbial mats can take place in aquatic environments through different mechanisms as a function of environmental conditions, microbial communities and nature of organic substrates. Carbonate precipitation associated with microbial mats and organic substrates in aqueous fluids, under favourable physico-chemical conditions, can be both the result of metabolic activity of alive microbes (Chafetz and Buczynski, 1992; Castanier et al, 1999; Knorre and Krumbein, 2000; biologically induced mineralization after Lowenstam and Weiner, 1989; Dupraz et al, 2009) and/or the result of mineralization of non living organic substrates with acidic macromolecules able to bind Ca 2+ and Mg 2+ ions (organomineralization after Reitner, 1993; Défarge and Trichet, 1995; Trichet and Défarge, 1995; Reitner et al, 1995ab; Défarge et al, 1996; Neuweiler et al, 1999; Reitner et al, 2000, 2001; Défarge et al, 2009; organomineralization sensu strictu and biologically influenced mineralization after Dupraz et al, 2009; organic-compound catalyzed mineralization after Franchi and Frisia, 2020). Organomineralization has been identified in association with various organic substrates such as microbial biofilm EPS (Extracellular Polymeric Substances), post-mortem encrustation of bacterial cells, sponge tissues or even abiotic organic compounds (Reitner, 1993; Reitner, 2004; Défarge et al, 2009).…”
Section: Introductionmentioning
confidence: 99%